2014
DOI: 10.3732/ajb.1400198
|View full text |Cite
|
Sign up to set email alerts
|

The African baobab (Adansonia digitata, Malvaceae): Genetic resources in neglected populations of the Nuba Mountains, Sudan

Abstract: Results indicated a rather positive effect with human intervention. The observed populations provide a promising gene pool and likely comprise ecotypes well-adapted to environmental conditions at the northern distribution range of the species, which should be considered in conservation and management programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Most studies of baobab population structure have focused on microsatellites Larsen & al., 2009;Munthali & al., 2013;Wiehle & al., 2014), plastid DNA (Leong Pock Tsy & al., 2009), or AFLPs ). However, it was previously suggested that A. kilima might be distinct from A. digitata based partly on ITS sequences , leading us to look for evidence of this in a broad sample of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of baobab population structure have focused on microsatellites Larsen & al., 2009;Munthali & al., 2013;Wiehle & al., 2014), plastid DNA (Leong Pock Tsy & al., 2009), or AFLPs ). However, it was previously suggested that A. kilima might be distinct from A. digitata based partly on ITS sequences , leading us to look for evidence of this in a broad sample of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of species' tetraploid nature, data analyses were challenging due to the unknown allele dosage of partial heterozygotes. We used a combined approach (see, e.g., Wiehle & Prinz et al, ), by transforming present alleles in a binary matrix to analyze the data in a dominant manner, and by estimating allele frequencies of partial heterozygotes in a codominant manner for population genetic indices based on Hardy–Weinberg equilibrium (Hardy, ; Weinberg, ).…”
Section: Methodsmentioning
confidence: 99%
“…The multipurpose tree species Adansonia digitata L., well-known as ‘baobab’, is one of the most important indigenous fruit trees of sub-Saharan Africa, with substantial social and economic importance [1,2]. The tree provides food, medicine and fibre, whereas almost all tree parts, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, owing to the fact that baobab is tetraploid, the analysis of genetic data and their interpretation requires more scrutiny than with diploid species [10]. Studies on baobab genetic resources have been reported from West African countries such as Benin, Ghana, Burkina Faso and Senegal [5,11,12], while East Africa is represented by studies from Malawi and Sudan [2,13]. In studies from Sudan and Malawi, microsatellite loci developed for A. digitata [14] were applied, while studies from West Africa used amplified fragment length polymorphism (AFLP) markers.…”
Section: Introductionmentioning
confidence: 99%